An integrity based radio frequency identification (RFID) method against reply attack - Hosseini, Seyed Mostafa Mir (2013)
Radio Frequency Identification (RFID) is a new in technology field. This emerging technology has been use in different applications. RFID systems have their own security challenges and this research is going to explore integrity attacks in RFID systems. Even though the previous related works have their own strength and weaknesses. The two factor authentication based method is proposed to prevent Replay attacks. In this method, necessary processes are mentioned, tag and the reader two factor authentication by using a security token and integrity would be guaranteed. It can prevent replay attack in RFID systems through using TOTP. In this additional security step legitimate and fake tag will be recognized. Integrity of tag information will be achieved. In addition, Replay attack is prevented by implementing one time password token. The significant attack such as Replay attack, Tracking attack, MITM attack, Spoofing attack, Impersonation, Cloning, Tampering, Forgery attacks can be achieved when attacker cannot generate a one-time password. This integrity based RFID method can be used in access control to prevent unauthorized access.